Assessing community health information systems: Evidence from child health records in food insecure areas of the Ethiopian highlands - Hirvonen, Kalle; Berhane, Guush; Assefa, Thomas (Springer, 2020)
Objectives: This study assessed the completeness of child health records maintained and collected within community health information system in Ethiopia. Methods: A household listing was carried out in 221 enumeration areas in food insecure areas of Ethiopia to determine the presence of a child less than 24-months. This list of children was then compared against the information stored at the local health posts. A household survey was administered to a sample of 2155 households that had a child less than 24-months of age to assess determinants and consequences of exclusion from the health post registers. Results: Out of the 10,318 children identified during the listing, 36% were found from the health post records. Further analysis based on the household survey data indicated that health posts that had adopted nationally recommended recordkeeping practices had more complete records (p < 0.01) and that children residing farther from health posts were less likely to be found from the registers (p < 0.05). Mothers whose child was found from the registers were more likely to know a health extension worker (p < 0.01), had a contact with one (p < 0.01), and their child was more likely to have received growth monitoring (p < 0.05). Conclusions for Practice: The incompleteness of the data collected at the health posts poses a challenge for effective implementation of the national health extension program and various complementary programs in Ethiopia.